Itaconate and obesity-related hormones promote tumor progression – new insights on metabolic dysfunction in early-onset colon cancer - Katharina M. Scheurlen; Jacob Hallion; Dylan L. Snook; Anne MacLeod; Robert J. Beal; Mary A. Parks; Andrew B. Littlefield; Eliah Hiken; Adrian T. Billeter; Jeannette Bensen; Jeremy T. Gaskins; Julia Chariker; et al. (Frontiers in Immunology)
IntroductionObesity is a strong risk factor for early-onset colon cancer (EOCC) and is associated with chronic inflammation largely mediated by macrophages. The macrophage-specific metabolite itaconate promotes growth in several types of cancer; however, its role in colon cancer (CC) is unknown. Here, we investigate a tumor promoting link between obesity-related hormones and itaconate within the NOTCH4-GATA4-IRG1 pathway in EOCC.MethodsPatient tissue (n=20) was obtained and qRT-PCR, ELISA, and mass spectrometry were performed to evaluate IRG1 expression (Human Immune-Responsive Gene 1, encoding ACOD1), ACOD1 expression (Cis-aconitate decarboxylase 1, enzyme producing itaconate), and itaconate concentration in human CC versus EOCC. RNA sequencing data from 5 sources in the USA and Europe were obtained to perform IRG1-related differential expression analysis (n=178), IRG1-related survival analysis (n=185), and differential expression analysis and survival analysis related to genes of the NOTCH4-GATA4-IRG1 pathway (n=371). Furthermore, tumor versus normal colon was compared and the interaction of tissue with sex, age, and body mass index (BMI) was investigated. A coculture model using two CC cell lines (HT-29 and SW480) and THP-1 cell line-derived M0 and M2-like macrophages was used to evaluate NOTCH4-GATA4-IRG1 pathway-related gene expression following treatment with obesity-related hormones (leptin, adiponectin) and itaconate derivatives.ResultsBoth ACOD1 and IRG1 expression were elevated in human CC tissue compared to adjacent normal colon tissue. Normal colon itaconate levels were higher in EOCC patients compared to that in older patients. Plasma itaconate levels in CC patients correlated with their BMI. Survival was decreased in IRG1-positive stage IV CC. IRG1-associated gene expression within the NOTCH4-GATA4-IRG1 pathway differed in CC versus normal colon tissue: GATA4, DLL4, VEGFA, and MAPK15 upregulation was associated with EOCC, while ABCG5 and GATA5 were downregulated in CCs and associated with higher BMI. Adiponectin and leptin treatment of macrophages cocultured with CC cells increased IRG1 expression.DiscussionObesity-related hormones can increase itaconate production in M2-like macrophages. IRG1 expression and the NOTCH4-GATA4-IRG1 pathway are associated with EOCC, BMI, and patient survival. As a macrophage metabolite affecting inflammation, itaconate may have a particular immunotherapeutic role in patients with EOCC.